Psychology and the study of opponents in the World Chess Championship (Original) (Revista científica Olimpia, 2025)
The duels for the World Chess Championship, with study material and a learning source for players, technicians and psychologists, since the fight begins before the first move is made, on the psychological and strategic design level of the match. As a problematic situation, although the role of psychology and the study of opponents in chess is recognized, historical-logical studies that show the evolution in these fields are not usually carried out. The scientific problem answers how does psychology and the study of opponents influence chess results at the highest level? And in the qualitative research, the following methods and procedures were used: Analysis-synthesis, inductive-deductive, historical-logical, bibliographic review and observation. The objective: Reflect about the role of psychology in the study of opponents and its influence on the result of the World Chess Championships. After studying eight duels that a good psychological profile and an efficient and multifactorial study of opponents is essential to succeed at the highest level.
Keywords: Psychology, study of opponents, Chess, analysis